Triple chemical derivatization strategy assisted liquid chromatography-mass spectrometry for determination of retinoic acids in human serum - Gong, Ge-Ge (2023)
Retinoic acids (RAs), an important class of fatty acid derived from vitamin A, are closely associated with various human diseases including cancer. Hence, determination of endogenous RAs would help to uncover the mechanisms underlying RAs-related diseases. However, accurate quantification of RAs is still a challenge due to their high structure similarity, low abundance in biological samples and the lack of isotope internal standards (ISs). In this study, a liquid chromatography-mass spectrometry (LC-MS) method with high-sensitivity and high-throughput was developed to simultaneously determine 5 RAs (all-trans-retinoic acid, 13-cis-retinoic acid, 9,13-cis-retinoic acid, all-trans-4-oxoretinoic acid and 4-hydroxy-retinoic acid) in human serum. In the method, three derivatization reagents, N, N-dimethylethylenediamine (DMED), d4-N,N-dimethylethylenediamine (d4-DMED) and 13C2-N,N-dimethylethylenediamine (13C2-DMED), were used for triple chemical derivatization of RAs, thus the detection sensitivity and analysis throughput of endogenous RAs could be achieved. Benefiting from the developed strategy, the analysis throughput was enhanced and the detection sensitivity of RAs was increased by 14-398 folds. The limits of quantification (LOQs) of RAs were found to be between 8.4 and 130 pg/mL, which were better than previously reported methods. Good linearities of RAs were obtained with determination coefficient (R2) ranging from 0.9774 to 0.9999. The intra- and inter-day relative standard deviations (RSDs) were below 11.7% and 12.7%, respectively, indicating the acceptable reproducibility of the method. Using the developed method, we successfully quantified 4 RAs (all-trans-retinoic acid, 13-cis-retinoic acid, 9,13-cis-retinoic acid and all-trans-4-oxoretinoic acid) in health controls and cancer patient serum samples. Furthermore, t-test analysis showed that the concentration of three RAs (all-trans-retinoic acid, 13-cis-retinoic acid and all-trans-4-oxoretinoic acid) in cancer patient serum samples were significantly decreased compared with health controls, which indicated that RAs might play an important role in the formation and development of cancer.